ANALISIS PENGARUH BERBAGAI FAKTOR TERHADAP PERTUMBUHAN EKONOMI DAN KETIMPANGAN WILAYAH DI PROVINSI LAMPUNG - Al Maisa Afifah Azzahwa; Fauzan Baihaqi; Mery Anggraini; Dinda Adelia; Alief Rakhman Setyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The main problem in this study is the existence of variations in economic growth across various districts/cities in Lampung Province and the possibility of regional inequality that can impact the distribution of development. The purpose of this study is to examine the pattern of economic growth in the regions and assess the level of regional inequality in Lampung Province in the period 2013–2018. The methodology applied is a quantitative descriptive analysis through the Klassen Typology to identify regional growth categories and evaluation of inequality using the Williamson Index and Theil Entropy Index with district/city GRDP data as a basis. The research findings conclude that 60% of the regions are in Quadrant I (developed and growing rapidly), 33.3% in Quadrant II (developed but experiencing pressure), and one region in Quadrant III, with no regions lagging behind. Regional inequality is classified as low with an average Williamson Index of 0.2679 and a Theil Index of 0.17567, although there is a tendency for increasing differences between regions. These results indicate that Lampung Province has demonstrated relatively good economic growth performance, but still requires attention to potential long-term inequality.